Numerical volume computation techniques in mining practice - Ferenc, Marcell; Havasi, István (Acta Agraria Kaposváriensis, 2010)
In the study after the introduction volume computation techniques used in the practice are overviewed briefly. Then the efficiency the methods given in the title is examined on known mathematical bodies (a cone and a pyramid). After that on the basis of a real mining example the formerly-mentioned computation methods are tested employing Surfer, Digiterra and AutoCAD Civil 3D programmes being well-known in mining practice. Finally, on the basis of the given results a proposal is made for expedient use in mining.